Chilean Berry Ugni Molinae Turcz. Fruit and Leaves Extracts with Interesting Antioxidant, Antimicrobial and Tyrosinase Inhibitory Properties - Valenzuela-Bascunan, X; Galotto-Lopez, M; Lopez de Dicastillo-Bergamo, A (Elsevier Ltd, 2017)
The knowledge of the biological properties of fruits and leaves of murta (Ugni molinae Turcz.) has been owned by native Chilean culture. The present study investigated the phenolic content, the antioxidant, antimicrobial and anti-tyrosinase activities of different murta fruit and leaves extracts to approach their uses on future food, pharmaceutical and cosmetic applications. Extractions of murta fruit and leaves were carried out under water, ethanol and ethanol 50%. Phenolic content of these extracts was measured through Folin Ciocalteu test and the antioxidant power by four different antioxidant systems (ORAC, FRAP, DPPH and TEAC assays) owing to elucidate the main mechanism of antioxidant. Some flavonoids, such as rutin, isoquercitrin and quercitrin hydrate were identified and quantified through HPLC analysis. Antimicrobial activity was determined measuring minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC) values against Escherichia coli and Listeria monocytogenes, and the effect of these extracts on L. monocytogenes was confirmed by flow cytometry. Highest contents of polyphenol compounds were obtained in hydroalcoholic extracts (28 ± 1 mg gallic acid/g dry fruit, and 128 ± 6 mg gallic acid/g dry leaves). The same trend was found for the values of biological properties: hydroalcoholic extracts showed the strongest activities. Leaves presented higher antioxidant, antimicrobial and anti-tyrosinase properties than murta fruit. Highest antioxidant activity values according to ORAC, FRAP, TEAC and DPPH were 80 ± 8 mg Trolox/g, 70 ± 2 mg Trolox/g, 87 ± 8 mg Trolox/g and 110 ± 12 mg Trolox/g, respectively, for murta fruit samples, and 280 ± 10 mg Trolox/g, 192 ± 4 mg Trolox/g, 286 ± 13 mg Trolox/g and 361 ± 13 mg Trolox/g, respectively, for murta leaves. These activities were confirmed by HPLC analysis that revealed highest presence of analyzed compounds on leaves hydroalcoholic extract. Regarding to antimicrobial analysis, hydroalcoholic leaves extract presented the highest activity presenting the lowest MIC value for L. monocytogenes (0.07 mg/mL). This extract also performed the highest anti-tyrosinase activity (CE50 values of 1.6 ± 0.3 (g/L) and 8.9 ± 1.2 (g/L) for leaves and fruit, respectively). © 2017 Elsevier Ltd